On the role of N.N. Bogolyubov in the development of the theory of nonlinear oscillations - Mitropolskiy, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
A review of N. N. Bogolyubov’s works on investigations in the theory of nonlinear oscillations is presented.